Correlation of age at seizure onset with GABAA receptor subunit and chloride Co-transporter configuration in Focal cortical dysplasia (FCD). (6th February 2023) - Sharma, Devina; Tripathi, Manjari; Doddamani, Ramesh; Sharma, M.C; Lalwani, Sanjeev; Sarat Chandra, P.; Banerjee Dixit, Aparna; Banerjee, Jyotirmoy
Graphical abstract: Highlights: Altered subunit configuration of GABAA receptors and modulation of NKCC1/KCC2 levels is associated with age at epilepsy onset in patients with FCD. Differential levels of α4/α1-containing GABAA receptors in cortical samples of FCD patients with early age at seizure onset (EO) and late age at seizure onset (LO). The ratio of GABA/glutamate neurotransmitters varied between EO and LO patients with FCD. Abstract: Focal cortical dysplasia (FCD) represents a group of malformations of cortical development, which are speculated to be related to early developmental defects in the cerebral cortex. According to dysmature cerebral development hypothesis of FCD altered GABAA receptor function is known to contribute to abnormal neuronal network. Here, we studied the possible association between age at seizure onset in FCD with the subunit configuration of GABAA receptors in resected brain specimens obtained from patients with FCD. We observed a significantly higher ratio of α4/α1 subunit-containing GABAA receptors in patients with early onset (EO) FCD as compared to those with late onset (LO) FCD as is seen during the course of development where α4-containing GABAA receptors expression is high as compared to α1-containing GABAA receptors expression. Likewise, the influx to efflux chloride co-transporter expression of NKCC1/KCC2 was also increased in patients with EO FCD as seen during brain development. In addition, we observed that the ratio of GABA/Glutamate neurotransmitters was lower in patients with EO FCD as compared to that in patients with LO FCD. Our findings suggest altered configuration of GABAA receptors in FCD which could be contributing to aberrant depolarizing GABAergic activity. In particular, we observed a correlation of age at seizure onset in FCD with subunit configuration of GABAA receptors, levels of NKCC1/KCC2 and the ratio of GABA/Glutamate neurotransmitters such that the patients with EO FCD exhibited a more critically modulated GABAergic network.